Determination of frying sunflower oil usage time for local potato samples by using microwave transmission line based sensors. (15th October 2020) - Erdoğan, Maide; Ünal, Emin; Özkan Alkurt, Fatih; Abdulkarim, Yadgar I.; Deng, Lianwen; Karaaslan, Muharrem
Highlights: Dielectric characterization and two different transmission line sensor designs. A linear increment of dielectric between 2.9 and 3.3 in 16 times frying. The resonance shifts on return loss-S11 around 5.45 GHz. Resonance shifts on S21 of 150–100-200 MHz at 4.4–5.4 and 7.6 GHz respectively. Proposed structures can be used to determine lifetime of fried oil sample. Abstract: Amount of oil usage time can be determined by microwave measurements instead of using complex laboratory equipments to measure oil parameters such as viscosity, base number, refractive index, acid numbers, density, water substances, etc. Microwave measurements are easy and offer clear results to indicate oil quality and lifetime. In microwave measurements, there are two main parameters: dielectric constant value "ε", and loss tangent value "tanδ" that can be used as indicators for identifying any material or medium which will be oil substances in our case. When the dielectric constant value "ε" of frying sunflower oil is measured, changes in the dielectric constant and loss tangent of the used oil relative to the unused pure sunflower oil can specify the presence of contaminant materials such as water and particles, or changes in the chemistry of the oil. In this study, we propose two different sensor structures to determine the usage amount of sunflower oil in frying. Before the sensor design, dielectric constants and loss tangent values of various time fried oil samples were measured in 4–8 GHz band. Each sensor structures designed as two port transmission line and operating in 4–8 GHz band. Designed first sensor has two advantages including the resonance shifts on return loss (S11) at around 5.45 GHz and another resonance shifts on transmission (S21) of 150 MHz, 100 MHz and 200 MHz at 4.4 GHz, at 5.4 GHz and at 7.6 GHz, respectively. The second sensor has a resonance shift only on transmission (S21) characteristic between the frequencies of 4 GHz and 6 GHz with approximately 100 MHz band. Finally, each sensor structures were fabricated and experimental measurements were conducted by using the vector network analyzer in microwave laboratory and accurate results were obtained and well match is observed with simulation results. According to experiment, proposed structures are reliable and also have advantages such as easy fabrication, low cost, high sensing performance and real time measurement. Designed sensors have higher sensing performances than its counterparts and they can be used to determine lifespan of frying oil samples in various applications.